Ultrastructure of spermiogenesis in Plagioscion squamosissimus (Teleostei, Perciformes, Sciaenidae) - Gusmao, P.; Foresti, F.; Quagio-Grassiotto, I (Churchill Livingstone, 1999)
Spermiogenesis in Plagioscion squamosissimus occurs in cysts. It involves a gradual differentiation process of spermatids that is characterized mainly by chromatin compaction in the nucleus and formation of the flagellum, resulting in the spermatozoa, the smallest germ cells. At the end of spermiogenesis, the cysts open and release the newly formed spermatozoa into the lumen of the seminiferous tubules, the spermatozoa do not have an acrosome and are divided into head, midpiece, and tail or flagellum, the spermatozoa of P. squamosissimus are of perciform type with the flagellum parallel to the nucleus and the centrioles located outside the nuclear notch. (C) 1999 Harcourt Publishers Ltd.
Keywords: Plagioscion squamosissimus; teleostei; ultrastructure; spermiogenesis; spermatids; spermatozoon